Adapting an integrated neglected tropical disease programme in response to COVID-19. (11th February 2021) - Clark, Amy; Hill, Becks; Bannerman, Ron; Wohlgemuth, Leah; Burrill, Jennifer; Agyemang, David; Genovezos, Chantelle
Abstract: The COVID-19 pandemic hit at a time when the Ascend West and Central Africa programme was nearing the end of its first year of a 3-y programme. This article reflects on key lessons learnt from the rapid adaptation of an integrated neglected tropical disease (NTD) programme to support COVID-19 responses in 11 countries. It shares the experiences of adopting a flexible and directive approach, leveraging the NTD network and relationships, and working in collaboration with multiple ministry departments, commercial sector partners and the UK Foreign Commonwealth Development Office to repurpose over £6 million of budget.